Development of A Cooperative Digitalization System to Improve Efficiency and Transparency - Pramono, Agung; Zulfikar (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
The rapid expansion of Indonesia’s palm oil sector has increased the importance of cooperatives in supporting the livelihoods of smallholder farmers. Despite their critical role, many cooperatives still depend on manual administrative practices, which often lead to slow reporting, fragmented records, and limited access to reliable information. This study responds to these issues by developing a web-based digital system designed to improve cooperative management and strengthen financial accountability. The research follows a Research and Development approach and applies the Extreme Programming method to ensure that system development remains flexible, iterative, and closely aligned with user needs. Field data were collected through interviews and direct observation at KUD Sawit Jaya UUO Petapahan Makmur Sejahtera. These inputs informed the design of three main system components: a digital member management module, an automated financial transaction module, and an interactive dashboard that presents real-time cooperative information. The system has been fully developed and adopted by the cooperative. Early use indicates clear improvements in administrative efficiency, accuracy of financial records, and transparency of information shared with members. Overall, the system provides a practical digital solution for rural cooperatives and offers a model that can be adapted by other smallholder-based organisations across Indonesia’s palm oil regions.